[2]Rotaxanes comprising a macrocylic Hamilton receptor obtained using active template synthesis: synthesis and guest complexation. Issue 9 (2nd October 2016) - Tron, Arnaud; Thornton, Peter J.; Kauffmann, Brice; Tucker, James H. R.; McClenaghan, Nathan D.
Abstract: A macrocyclic ring comprising multiple hydrogen-bonding sites as well as metal-chelating sites is shown to play the role of ligand in active templated, copper-catalysed [2]rotaxane formation via Huisgen and Glaser reactions. The crystallographic structure and copper ion binding studies are provided for the free macrocycle, along with molecular modelling, barbital, N, N′-trimethyleneurea and copper (I) binding information for the new rotaxanes. Abstract :